Analysis Legal Action Criminal Forgery Marriage Without Permission Wife First - Selviana Nasruddin; Dachran Bustamin; Andi Darmawansya Tenriliweng (COMPENDIUM OF JUDGE MADE LAW, 2025)
This research aims to analyze the legal framework of Indonesian positive law regarding the criminal act of marriage falsification without the first wife's consent and evaluate the judicial considerations in Decision Number 374 K/Pid/2011. The research method used is normative juridical, utilizing statutory, comparative, and conceptual approaches. Data sources include primary legal materials such as legislation and court decisions, and secondary legal materials from literature and previous research. The findings indicate that marriage falsification without the first wife's consent violates Article 279 of the Indonesian Criminal Code (KUHP) and may also fall under Article 263 regarding document forgery. From an Islamic law perspective, polygamy is permitted but requires justice and the first wife's consent. Decision Number 374 K/Pid/2011 highlights judicial considerations regarding the criminal elements and the impact on victims. This study recommends harmonizing positive law and Islamic law to ensure better legal certainty and strengthening polygamy regulations to prevent similar violations in the future.